Violência intrafamiliar : possibilidades e limites na proteção de crianças e adolescentes - Aguiar, Tânia Cristófolli de (2016)
This thesis aims at evaluating public policies to protect children and adolescents victims of family violence and the interface with the Rights Guarantee System (SGD) of Children and Adolescents in the city of Canela / RS. In view of these aspects, it will contribute to the implementation of public policies for children and adolescents whose rights have been violated in the family, as well as on preventive actions to situations of violence. The accompanying theoretical categories of reality were about: the historical background of social protection of children and adolescents in Brazil; intrafamily violence against children and adolescents; the Rights Guarantee System of children and adolescents; public policy and evaluation of public policies and social programs. a case study of formative evaluative nature with mixed approach, guided by critical dialectical method was performed. The mixed approach involved the collection and analysis of quantitative and qualitative data, as well as their integration and joint discussion allowing them to be better exploited and used. The qualitative approach was dominant and sought the meaning of the DGS of Children and Adolescents in the political, ideological and cultural dimensions to social actors within it. It analyzed how these ideas materialize in the care of children and adolescents victims of family violence, and the perception of the families of interventions DGS actors of Children and Adolescents in their daily life. The mixed approach used concomitant inlaid design of the dominant model with a qualitative focus. In this design, the method that has lower priority is inserted in what is principal, to answer questions relevant to the research topic (SAMPIERI, 2013). Built up quantitative and qualitative indicators, as of guiding questions that signal aspects of reality studied. They were statistically worked with qualitative strategies to measure values, beliefs and thoughts that are expressed in the practice of the subject. The collection of quantitative data sought classification of violence committed against children and adolescents with the victims, perpetrators, manifestations of violence and forwarded protective measures. It was a cross sectional study with documentary source. To collect qualitative data were used to semi-structured interviews and focus group. The subjects of qualitative approach were the subjects that operationalize the DGS of Children and Adolescents, linked to public policy in the axes of the promotion, defense and social control, and the families served. The systematization and interpretation of qualitative data from interviews and focus groups were conducted through content analysis, defined by Bardin (1977). The results identify women as the main aggressors of their children, having preponderance negligence, which, according to the measures adopted, suggest criminalization of poverty and the institutionalization of children and adolescents, contrary to the legal provisions. The failure and the lack of structure of human, physical, administrative and cofinancing of the agencies and surveyed DGS operator services negatively impact the care. The precariousness of working conditions interfere with the implementation of the powers and duties of the organs, among these, diagnosis of infantojuvenil reality, formulation and implementation of public policies for children and adolescents in the promotion and defense of their rights. Some of the results obtained with this research hurt the primacy of care in the public sphere and the constitutional principle of absolute priority of children and adolescents. The presentation of the survey results will be carried out through seminars open to the community, especially to social subjects identified in this project: families, professionals and operators and governing bodies of the DGS of Children and Adolescents.